(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Feminism as a phenomenon has gained widespread recognition in Africa over the course of the recent decades. The perception of women who self-identify as feminists are often characterized as extremist, as their beliefs and actions are seen as contravening against African customs and traditions. This study diligently examines the exploitation and oppression endured by women, effectively illustrating the oppressive condition that leads them to be psychological wrecks. As a result, people become aware of the importance of institutionalising societal reforms in order to improve the status of women in patriarchal society. The finding of this study implicitly encourages the collaboration between men and women as an essential ideology in the current social and political transitions taking place in the African continent. The methodology employed by the central character in the literary work to emancipate herself could conceivably be regarded as revolutionary. The utilization of African Reformist Feminism serves as the theoretical framework for the critical examination of the novel. Indeed, it is an undeniable verity that women endure subjugation, dehumanization, and a multitude of cruelties perpetrated by men. Nevertheless, within the purview of this feminist paradigm, one must also acknowledge certain affirmative facets inherent in patriarchal societies, which foster the cultivation of harmonious cohabitation between men and women. Consequently, reformist feminism strategically employs the inclusion of positive male characters in its discourse, with the aim of fostering a transformative shift in the mindset of men who harbour repressive inclinations towards women. By presenting men as potential agents of change, reformist feminism seeks to challenge and dismantle the existing patriarchal power structures, urging men to perceive women as equal and indispensable partners in the collective progress of civilization.